Jews, Christians, and the discourse on images before Iconoclasm - Sivertsev, Alexei 1973- (Cambridge, United Kingdom New York, NY Cambridge University Press, 2024)
"Explores the rise of image as a rhetorical category in Jewish and Christian literature originating between the sixth and eighth centuries. This book demonstrates how Jewish texts serve as an important witness to the formation of image discourse and associated practices of image veneration" --
Dissimilar Similarities -- The History of a Late Antique Motif -- Jacob's Dream and Relic Veneration -- God's Impossible Form -- Articulating the Impossible.
Includes bibliographical references and index
Keywords: Yannai -- Criticism and interpretation; Jacob -- (Biblical patriarch); Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Visual perception -- History -- To 1500; Piyutim -- History and criticism